Light‐Emitting Diodes: Monolithic Flexible Vertical GaN Light‐Emitting Diodes for a Transparent Wireless Brain Optical Stimulator (Adv. Mater. 28/2018). Issue 28 (9th July 2018) - Lee, Han Eol; Choi, JeHyuk; Lee, Seung Hyun; Jeong, Minju; Shin, Jung Ho; Joe, Daniel J.; Kim, DoHyun; Kim, Chang Wan; Park, Jung Hwan; Lee, Jae Hee; Kim, Daesoo; Shin, Chan‐Soo; et al.
Abstract : In article number1800649, Keon Jae Lee and co‐workers demonstrate high‐performance, transparent, flexible, GaN vertical micro‐light‐emitting‐diodes (f‐VLEDs) via a simple fabrication process. The wireless power supply system is successfully realized by transferring the electrical energy to the f‐VLEDs, which realizes the possibility of a transparent wireless brain optical‐stimulation system.